Ethnopharmacognastical Investigation on Ipomoea pes-tigridis Linn - G. Penchala Pratap,; G. Sudarsanam,; B.Jyothi,; K. Michel David, (International Journal of Phytomedicine, 2011)
The present investigation was undertaken to analyze the Pharmacognostical, physicochemical and preliminary phytochemical profile in the leaves and roots of Ipomoea pes-tigridis Linn. with the back ground of Ethnic importance. This plant is used by the tribes of Nellore district as a single drug remedy to treat as Laxative and skin diseases. In the present work the leaf and root part of the plant were subjected to various microscopical and physico- preliminary phyto chemical evaluations. In the microscopical studies, the different cell structures and arrangements were studied. Physicochemical parameters like loss on drying, total ash value, acid insoluble ash, water insoluble ash, various extractive values etc., were carried out. Further, qualitative tests for various functional groups like Triterpenoids, alkaloids, glycosides etc..., were carried out.